Tantangan Guru Reguler dalam Pendidikan Inklusif dan Pengembangan Modul Ajar sebagai Solusi Pembelajaran ABK di Sekolah Dasar - LA ODE HERIN; Homi Apriani; Rosita; Sylva Sagita; Syarif Sumantri (STKIP Subang, 2025)
ABSTRACT This study aims to identify the obstacles faced by regular teachers in implementing inclusive education and to develop an inclusive teaching module as a practical solution to enhance the learning effectiveness for Children with Special Needs (ABK) in Elementary Schools. Inclusive education confronts major challenges, including the lack of understanding and pedagogical competence among regular teachers in handling ABK, compounded by minimal support from Special Assistance Teachers (GPK). This descriptive qualitative research, employing a qualitative case study design at SDN Cempaka Putih Barat 03, Jakarta Pusat, involved three class teachers and seven ABK (slow learners and borderline). The findings indicate that teachers struggle to adjust the pace of material, especially abstract concepts, for ABK, and the existing teaching materials are general. As a solution, an inclusive teaching module was developed with tiered learning objectives, which proved to be a relevant pedagogical approach for differentiating assessment and learning attainment. The module’s implementation, supported by a teaching team approach, increased ABK engagement. However, effectiveness remains limited by the regular teachers' basic competence in providing specific individual interventions. Therefore, successful inclusive learning necessitates a combination of flexible teaching materials, educator collaboration, and sustained professional support from GPK. Keywords: Inclusive Education, Regular Teacher, Children with Special Needs (ABK), Inclusive Teaching Module, Tiered Learning Objectives. ABSTRAK Penelitian ini bertujuan mengidentifikasi hambatan yang dialami guru reguler dalam penerapan pendidikan inklusif serta mengembangkan modul ajar inklusif sebagai solusi praktis untuk meningkatkan efektivitas pembelajaran Anak Berkebutuhan Khusus (ABK) di Sekolah Dasar. Pendidikan inklusif menghadapi tantangan utama berupa kurangnya pemahaman dan kompetensi pedagogis guru reguler dalam menangani ABK, diperburuk dengan minimnya dukungan Guru Pendamping Khusus (GPK). Penelitian kualitatif deskriptif dengan desain studi kasus kualitatif ini dilakukan di SDN Cempaka Putih Barat 03, Jakarta Pusat, melibatkan tiga guru kelas dan tujuh ABK (slow learner dan borderline). Hasil penelitian menunjukkan guru kesulitan menyesuaikan kecepatan materi, terutama konsep abstrak, untuk ABK, dan perangkat pembelajaran yang ada masih bersifat umum. Sebagai solusi, dikembangkan modul ajar inklusif dengan tujuan pembelajaran berjenjang yang terbukti menjadi pendekatan pedagogis relevan untuk diferensiasi asesmen dan capaian belajar. Implementasi modul yang didukung pendekatan teaching team meningkatkan keterlibatan ABK. Namun, efektivitas masih dibatasi oleh keterbatasan kemampuan dasar guru reguler untuk intervensi individual. Oleh karena itu, keberhasilan pembelajaran inklusif memerlukan kombinasi modul ajar yang fleksibel, kolaborasi pendidik, dan dukungan profesional berkelanjutan dari GPK. Kata Kunci: Pendidikan Inklusif, Guru Reguler, Anak Berkebutuhan Khusus (ABK), Modul Ajar Inklusif, Tujuan Pembelajaran Berjenjang.